ANN ROE'S CAREER GUIDANCE MODEL FOR STUDENT CAREER PLANNING - Sasrianis; Daharnis; Ifdil (Yayasan Amanah Nur Aman, 2025)
This study aims to explore the application of Ann Roe's theory in student career guidance, particularly in interest- and aptitude-based career planning. Ann Roe's theory highlights the relationship between childhood experiences, parenting, and individual career preferences. Using the literature study method, this research examines various relevant literature to understand the principles of Ann Roe's theory and how this theory can be applied in career guidance services in the digital era. The results show that Ann Roe's theory provides a comprehensive approach to help students understand their potential and make informed career decisions. The integration of technology in career guidance services based on Ann Roe's theory is one of the important strategies. Artificial intelligence-based career assessment applications, interactive digital media, and structured guidance modules proved effective in improving students' understanding of various career options. In addition, collaboration between counselors, schools, and parents plays a key role in creating a supportive environment for students' career planning. By adopting this approach, career guidance services can help students prepare for the challenges of the ever-evolving world of work. This study concludes that Ann Roe's theory remains relevant in providing personalized and data-driven career guidance.